Perencanaan Lanskap Kecamatan Pangkalan Karawang sebagai Kawasan Wisata Terpadu Berbasis Masyarakat (Community Based Tourism) - Zahra, Haifa Az; Makalew, Afra Donatha Nimia; Budiarti, Tati (Jurnal Lanskap Indonesia, 2024)
Pangkalan District has been designated as a tourism destination by department of tourism and culture of Karawang Regency. However, facilities and accessibility for visitors, and participation of human resources in planning tourism destination still not optimal. The objective of this study is to create landscape plan for community-based tourism (CBT) at Pangkalan district as an integrated tourist area in Karawang Regency. This study was conducted in four villages of Pangkalan, consists of Jatilaksana, Medalsari, Tamanmekar, and Tamansari with the total area 6.637 ha. The analysis in this study applied spatial and qualitative methods using assessment and scoring the variable criteria of landscape tourism. The results showed that Pangkalan has the potential to be developed based on physical-biophysical conditions (topography, climate, soil, hydrology, land cover) and existing tourism. The community's acceptability of integrated tourism planning at Pangkalan has very good response with a suitability classification of S1 (very suitable) and S2 (quite suitable). The planning is divided into three zones consisting of an intensive tourism development zone (5324.57 Ha), a semi-intensive tourism development zone (374.15 Ha), and a non-intensive development zone (938.38 Ha). Pangkalan is a planned large carrying capacity area of 65,614 people per day. The recommendation for developing an integrated tourism base in Karawang is to establish a management body to run the operations of the area. Keywords: community acceptability, integrated tourism, landscape planning, Pangkalan